INCREASING DISCLOSURE OF CARBON EMISSIONS WITH CORPORATE GOVERNANCE AS A MODERATION VARIABLE (STUDY OF MANUFACTURING COMPANIES LISTED IN IDX IN 2017-2021) - Rihan Mustafa Zahri; Erma Wulan Sari; Ahmad Nur Aziz; Desy Nur Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to test corporate governance: independent commissioners, independent audit committees, and gender diversity moderate the influence of company size on carbon emission disclosure. The data collection method used purposive sampling with a sample of 89 manufacturing companies listed on the IDX in 2017-2021. In hypothesis testing using Moderated Regression Analysis. The results of this research show that company size has an effect on carbon emission disclosure and is strengthened by the existence of a moderating variable, namely corporate governance consisting of independent commissioners, independent audit committees, and gender diversity.